Serratia marcescens contains a heterodimeric HU protein like Escherichia coli and Salmonella typhimurium. - Oberto, J (1996)
Homologs of the dimeric HU protein of Escherichia coli can be found in every prokaryotic organism that has been analyzed. In this work, we demonstrate that Serratia marcescens synthesizes two distinct HU subunits, like E. coli and Salmonella typhimurium, suggesting that the heterodimeric HU protein could be a common feature of enteric bacteria. A phylogenetic analysis of the HU-type proteins (HU and IHF) is presented, and a scheme for the origin of the hup genes and the onset of HU heterodimericity is suggested.